MODEL KOLABORASI LINTAS SEKTOR DALAM MENGHADAPI BEBAN GANDA PENYAKIT DI TINGKAT KOMUNITAS PADA ERA TRANSISI EPIDEMIOLOGI : TINJAUAN LITERATUR - Ni Rai Sintya Agustini; Eka Lutfiatus Solehah; Putu Ayu Lestarini; Zainudin Efendi; Desak Putu Risna Dewi (Journal of Innovation Research and Knowledge, 2026)
The epidemiological transition in Indonesia is characterized by a shift in disease patterns from those predominantly dominated by infectious diseases to an increasing prevalence of non-communicable diseases, without a significant decline in communicable disease cases. This situation has led to the phenomenon known as the double burden of disease, in which communicable and non-communicable diseases coexist within the same population. This condition increases the complexity of the health system, as it requires promotive, preventive, and curative approaches that must be implemented simultaneously and in a coordinated manner, particularly at the community level as the frontline of primary health care. This study aims to analyze the dynamics of the double burden of disease and to explore a community-based cross-sectoral collaboration model as a strategic approach to addressing the shifting disease patterns. The method employed was a literature review analyzing national and international journal articles published over the past six years through scientific databases focusing on the double burden of disease, behavioral risk factors, community-based health interventions, and multisectoral approaches to health care. The findings indicate that urbanization, lifestyle and dietary changes, increasing behavioral risk factors, and the high prevalence of infectious diseases such as HIV and tuberculosis further exacerbate the complexity of the double burden faced by Indonesian communities. Community-based interventions have proven effective in improving early detection and promoting behavioral change; however, their success largely depends on collaboration among the health sector, local governments, the education sector, and active community participation. Integrating communicable and non-communicable disease services within the primary health care system is a crucial strategy for creating a flexible and sustainable health response. Therefore, strengthening intersectoral collaboration through program integration, policy alignment, and community empowerment is essential as a structured approach to addressing the double burden of disease during the epidemiological transition.